Cognitive Correlates of Different Mentalizing Abilities in Individuals with High and Low Trait Schizotypy: Findings from an Extreme-Group Design - Kocsis-Bogár, Krisztina; Kotulla, Simone; Maier, Susanne; Voracek, Martin; Hennig-Fast, Kristina (Frontiers in Psychology, 2017)
Mentalizing or Theory of Mind (ToM) deficits in schizophrenia have been studied to great extent, but studies involving samples of trait schizotypy yield ambiguous results. Executive functions like cognitive inhibition, cognitive flexibility, and agency are all prerequisites of mentalizing, and it is assumed that the impairment of these functions contributes to ToM deficits in schizophrenia. Whether these impairments influence the ToM performance of people with high trait schizotypy remains unclear. Although impaired self-agency has repeatedly been identified in people with schizotypy, its role in mentalizing is yet to be investigated. The main aim of this study was to explore whether deficits in cognitive and affective ToM can be found in high trait schizotypy, and to identify in what way these deficits are related to the positive and negative dimensions of schizotypy. The secondary aim was to examine whether these deficits correlate with executive functions. Based on the dimensional view of the schizophrenia spectrum, an extreme-group design was applied to non-clinical volunteers demonstrating high (N = 39) and low (N = 47) trait schizotypy. Affective and cognitive ToM were investigated using the Movie for Assessment of Social Cognition (MASC), a sensitive and video-based measurement. Cognitive inhibition was assessed using the Stroop Test, and cognitive flexibility was analyzed using the Trail Making Test. Agency was measured using a computerized self-agency paradigm. Participants in the high-schizotypy group performed significantly worse in the affective ToM task (d = 0.79), and their overall ToM performance was significantly impaired (d = 0.60). No between-group differences were found with regards to cognitive ToM, executive functions and self-agency. Cognitive flexibility correlated negatively with positive schizotypy, and contributed to a worse overall and affective ToM. Impaired cognitive inhibition contributed to undermentalizing-type errors. It was found that non-clinical participants with high trait (positive) schizotypy – especially those with slight executive-function deficits – may have difficulties in understanding the emotional state of others and consequently in functioning in social situations.